MEASURING THE SUSTAINABILITY OF RED CHILI AGRIBUSINESS SYSTEM IN NORTH SUMATERA PROVINCE, INDONESIA - Novita, Desi; Supriana, Tavi; Sirozujilam, Sirozujilam; Lubis, Satia Negara (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Sustainable agriculture is an important factor in preserving sustainable development in an area. Red chili is a commodity that has a strategic role in the agricultural sector. This research aims to measure the endemic index in the red chili agribusiness system in North Sumatera Province. Data collection was carried out through in-depth interviews involving farmers, marketers, extension workers, and local governments using five dimensions of climbing. The data analysis method used was Multi-Dimensional Scaling (MDS), called RAP-Chili (Rapid Appraisal for Chili). The results show that the combined index for the red chili agribusiness system in this province is quite sustainable, with an index value of 58.94. Only one dimension is included in the high desire index level (78.35), namely the environmental dimension. Meanwhile, the other four dimensions are at the level of the quite desirable category, namely the economic dimension (52.82), the socio-cultural dimension (57.30), the partnership dimension (54.24), and the institutional dimension (51.98). Overall performance can be improved by making improvements in each dimension. Therefore, policy planning for developing the red chili agribusiness system must improve weak indicators and impact existing dimensions. Environmental aspects regarding land suitability, climate, and fertility must continue to be improved, considering that agriculture in Indonesia is still very dependent on natural resource factors.